WASTEWATER TREATMENT OF BATIK MICRO, SMALL, AND MEDIUM ENTERPRISES FOR CLEAN WATER CONSERVATION - Buwono, Haris Puspito; Suharti, Profiyanti Hermien; Puspitasari, Etik; Susanto, Susanto; Takwim, R. N. Akhsanu; Sulasari, Ayu; Ardiansyah, Rizky; Fadhilah, Alfira Insani; Jalaluddin, Agus (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Batik wastewater generated by micro-scale industries typically contains high organic loads, intense coloration, and fluctuating pH, exceeding national discharge limits. This study aims to design, install, and evaluate a simple pilot-scale wastewater treatment plant (WWTP) using a coagulation–filtration–adsorption process for UMKM Batik Ulur Wiji in Indonesia. Wastewater quality was analyzed before and after treatment for pH, BOD, COD, TSS, TDS, turbidity, and color referring to Indonesian Ministry of Environment Regulation No. 5/2014. The results show a substantial improvement in water quality, with COD reduced from 857 to 112 mg/L and BOD from 358 to 68 mg/L. Turbidity decreased from 218 to 14 NTU, and color removal was visually significant. The treated effluent met key parameters for non-potable reuse. A partner satisfaction survey revealed increased environmental awareness, full operational understanding of WWTP, and long-term commitment to system use. This study demonstrates that simple low-cost treatment units are effective for batik wastewater management in micro-industries and provide a replicable model for community-based environmental interventions.